Using a Robot to Address the Well-Being, Social Isolation, and Loneliness of Care Home Residents via Video Calls: Qualitative Feasibility Study - Lise Birgitte Holteng Austbø; Ingelin Testad; Martha Therese Gjestsen (JMIR Formative Research)
Abstract BackgroundAbout 40,000 people are living in Norwegian care homes, where a majority are living with a dementia diagnosis. Social isolation and loneliness are common issues affecting care home residents’ quality of life. Due to visitation restrictions during the pandemic, residents and family members started using digital solutions to keep in contact. There is no framework or guidelines to inform the uptake and use of technologies in the care home context, and this often results in non-adoption and a lack of use after the introduction phase. Hence, there is a great need for research on the feasibility of a robot that can facilitate video communication between residents and family members. ObjectiveThis study aimed to (1) introduce video communication through a robot to address social isolation and loneliness in a care home during a period of 6 weeks and (2) identify elements central to the feasibility concerning testing and evaluating the use of the robot. MethodsThree focus group interviews were undertaken: 1 with family members (n=4) and 2 with care staff (n=2 each). The informants were purposely selected to ensure that they had the proper amount of experience with the robot to have the ability to inform this study’s objectives. The focus group interviews were tape-recorded and transcribed verbatim, then subsequently analyzed using systematic text condensation. ResultsThe data analysis of focus group interviews and individual interviews resulted in three categories: (1) organizing the facilitation of video calls, (2) using a robot in dementia care, and (3) user experience with the robot. ConclusionsVideo communication in care homes is a feasible alternative to face-to-face interactions, but it depends on organizational factors such as information flow, resources, and scheduling. In dementia care, the user-friendly robot supports person-centered care through tailored social interaction. Both family members and staff express enthusiasm for video calls as an option and see its potential for future use.